The Relationship Between the Serum Anion Gap and All-Cause Mortality in Acute Pancreatitis: An Analysis of the MIMIC-III Database - Gong F (International Journal of General Medicine, 2021)
Fang Gong,1 Quan Zhou,2 Chunmei Gui,1 Shaohua Huang,1 Zuoan Qin3 1Department of Intensive Care Unit, The First People’s Hospital of Changde, Changde City, Hunan Province, 415000, People’s Republic of China; 2Department of Science and Education Section, The First People’s Hospital of Changde, Changde City, Hunan Province, 415000, People’s Republic of China; 3Cardiovascular Medicine Department, The First People’s Hospital of Changde, Changde City, Hunan Province, 415000, People’s Republic of ChinaCorrespondence: Fang GongDepartment of Intensive Care Unit, The First People’s Hospital of Changde, 818 Renmin Road, Changde City, Hunan Province, 415000, People’s Republic of ChinaTel +86-0736-7788035Email gficu2009@163.comPurpose: We aimed to investigate the relationship between the serum anion gap (AG) and all-cause mortality in patients with acute pancreatitis (AP) in intensive care units (ICUs).Patients and Methods: In this retrospective cohort analysis, data of patients with AP were extracted from the Medical Information Mart for Intensive Care database (version III). We collected the maximum serum AG value within the first 24 hours of ICU admission. The main outcome was 90-day all-cause mortality. A multivariate Cox proportional hazard regression model was used to examine the association between the serum AG and mortality. The restricted cubic spline curve was used to confirm a non-linear relationship between serum AG values and mortality.Results: Of the 279 patients included in the study, 87 (31.18%) died. The serum AG value was positively associated with 90-day all-cause mortality (hazard ratio [HR] 1.08, 95% confidence interval [CI] 1.02– 1.14), after adjusting for age, sex, alcohol consumption, congestive heart failure, diabetes mellitus, hypertension, eGFR, albumin, and the SOFA score. There was a non-linear relationship between serum AG values and mortality after adjusting for potential confounders. We used a two-piecewise regression model to obtain a threshold inflection point value of 13.8 mmol/L. The HR and the 95% CI on the left inflection point were 0. 82 (0.61– 1.09; p = 0.1719), and on the right inflection point were 1.15 (1.08– 1.23; p < 0.0001).Conclusion: The relationship between all-cause mortality in patients with acute pancreatitis and serum AG values was non-linear. All-cause mortality and serum AG values were positively correlated when the serum AG value was > 13.8 mmol/L.Keywords: anion gap, all-cause mortality, acute pancreatitis, MIMIC III database